When I feel afraid - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit Pub., 2003)
Explains that many things can be frightening and provides examples of what one can do to feel less afraid, such as asking for help from a person one trusts. Includes information and extension activities for parents or teachers.
Keywords: Fear in children -- Juvenile literature; Conduct of life; Fear